2022
DOI: 10.1111/rsp3.12518
|View full text |Cite
|
Sign up to set email alerts
|

Will COVID‐19 hinder or aid the transition to sustainable urban mobility? Spotlight on Portugal’s largest urban agglomeration

Abstract: This study discusses the possible effects of two major COVID‐19 disruptions – that is, the widespread adoption of working from home and the ‘bio‐security’ fear affecting public transport – on travel patterns in Lisbon urban agglomeration. Drawing on evidence from the literature on the effects of teleworking on travel demand and the determinants of public transport, together with the analysis of travel data before and during the pandemic, the study concludes that the pandemic may hinder, more than aid, the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“… 2021 ; Jenelius and Cebecauer 2020 ; Wielechowski et al. 2020 ; Melo 2022 ; Rasca et al. 2021 ; Jiang and Cai 2022 ).…”
Section: Introductionunclassified
“… 2021 ; Jenelius and Cebecauer 2020 ; Wielechowski et al. 2020 ; Melo 2022 ; Rasca et al. 2021 ; Jiang and Cai 2022 ).…”
Section: Introductionunclassified
“…One of the most relevant aspects in the evolution of mobility patterns throughout the pandemic is that reduction in travel flows has not been uniformly distributed across transport modes (Pereira et al 2021). While public transit has suffered steep declines in ridership (Tirachini and Cats 2020), the use of private vehicles for various purposes has nearly recovered compared to pre-pandemic levels (Melo 2022). Within this context, since the beginning of the pandemic, it has been speculated that COVID's impacts on mode split can be an opportunity for increasing the use of active modes, such as walking and cycling (Nurse and Dunning 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the beginning of the pandemic, it has been speculated that these large impacts on travel patterns can be a pivotal point for the renaissance of active modes of travel (Nurse and Dunning 2020). Although nowadays there is considerably less travel to work, with many employers still encouraging telecommuting, the use of private vehicles for various purposes has nearly recovered compared to pre-pandemic levels (Melo 2022). In this context, it is still not clear if the large increase in telecommuting during the lockdown periods has truly led to more use of active modes of travel for non-work purposes or the opposite.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this effect, some United States studies (Brueckner et al, 2023; Ramani & Bloom, 2021) found that the pandemic essentially led to a ‘donut’ effect in housing where the central ring of cities is deserted in favour of the suburbs. Melo (2022) found, unsurprisingly, that the pandemic setback public transport and sustainable urban mobility. This is a phenomenon which may quite well be true for India too.…”
Section: Introductionmentioning
confidence: 99%